Diagnostic Accuracy of Cadmium Zinc Tellurite (CZT) Detector-Based Dynamic Single Photon Emission Computed Tomography (D-SPECT) Myocardial Perfusion Imaging (MPI) in the Evaluation of Coronary Artery Disease (CAD) - Saleem, Husnain; Muhammad Inamullah Nouman; Zaigham Salim Dar; Muhammad Adil; Raza, Mehdi; Muhammad Atif (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the diagnostic accuracy of CZT detector-based dynamic SPECT MPI for detecting coronary artery disease (CAD), using coronary angiography as the reference standard. Study Design: Cross-sectional Observational Study. Place & Duration of Study: Department of Nuclear Cardiology, AFIC/NIHD, Rawalpindi, Pakistan, from Jan to Jun 2024. Methodology: A total of 198 patients who underwent coronary angiography within three months of a D-SPECT MPI were included. Dynamic SPECT MPI was performed using a CZT detector-based camera following 99mTc-Sestamibi injection during rest and stress phases. Stress imaging incorporated Adenosine infusion. Myocardial blood flow (MBF) and myocardial flow reserve (MFR) values were calculated. An MFR value <2 indicated CAD. Coronary angiography, interpreted by two cardiologists. Results: Of 198 patients, 167 (84.3%) were males and 31 (15.7%) were females, with a mean age of 56.03 ±11.83 years. D-SPECT MPI diagnosed CAD in 70 (35.4%) patients, while the actual number of patients having CAD as diagnosed by coronary angiography was 74 (37.4%). The calculated sensitivity, specificity, PPV, NPV, and diagnostic accuracy of D-SPECT MPI, keeping coronary angiography as the gold standard, were 87.8%, 95.9%, 92.8%, 92.9%, and 92.9%, respectively. Conclusion: This single-center study demonstrates that CZT-based dynamic SPECT MPI offers shorter imaging time, less radiation exposure, and cost-effectiveness, making it a valuable non-invasive diagnostic modality. The system’s enhanced resolution and faster imaging acquisition contribute to its clinical utility.